Long Time Well-Posedness of the MHD Boundary Layer Equation in Sobolev Space (Analysis in Theory and Applications, 2022)
In this paper, we study the long time well-posedness of 2-D MHD boundary layer equation. It was proved that if the initial data satisfies$$\|(u_0,h_0-1)\|_{H_{μ}^{3,0}\cap H_{μ}^{1,2}}\le ε,$$ then the life span of the solution is at least of order $ε^{2-η}$ for $η>0$.